Taking the High Ground: The archaeology of Rapa, a fortified island in remote East Polynesia (Terra Australis 37) - Anderson, Atholl (Terra Australis, 2012)
This volume brings the remote and little known island of Rapa firmly to the forefront of Polynesian archaeology. Thirteen authors contribute 14 chapters, covering not only the basic archaeology of coastal sites, rock shelters, and fortifications, but faunal remains, agricultural development, and marine exploitation. The results, presented within a chronology framed by Bayesian analysis, are set against a background of ethnohistory and ethnology. Highly unusual in tropical Polynesian archaeology are descriptions of artefacts of perishable material. Taking the High Ground provides important insights into how a group of Polynesian settlers adapted to an isolated and in some ways restrictive environment.